2013
DOI: 10.2196/jmir.2613
|View full text |Cite
|
Sign up to set email alerts
|

Collection and Visualization of Dietary Behavior and Reasons for Eating Using Twitter

Abstract: BackgroundIncreasing an individual’s awareness and understanding of their dietary habits and reasons for eating may help facilitate positive dietary changes. Mobile technologies allow individuals to record diet-related behavior in real time from any location; however, the most popular software applications lack empirical evidence supporting their efficacy as health promotion tools.ObjectiveThe purpose of this study was to test the feasibility and acceptability of a popular social media software application (Tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(47 citation statements)
references
References 17 publications
0
45
0
2
Order By: Relevance
“…From the digital footprints left by individuals on services such as Twitter and Facebook, researchers can identify temporal and geographic patterns in a wide range of health behaviours, including smoking [9], drinking alcohol [10] and eating [11]. Specific approaches to utilizing social media data vary, from using occurrences of specified keywords (e.g.…”
Section: Social Mediamentioning
confidence: 99%
“…From the digital footprints left by individuals on services such as Twitter and Facebook, researchers can identify temporal and geographic patterns in a wide range of health behaviours, including smoking [9], drinking alcohol [10] and eating [11]. Specific approaches to utilizing social media data vary, from using occurrences of specified keywords (e.g.…”
Section: Social Mediamentioning
confidence: 99%
“…Hingle and colleagues [56] collected 1,756 food-related hashtags via Twitter across all participants over 3 days. In Seto and colleagues' [59] 6-day study, 72 food items were reported via video per participant.…”
Section: Data Collection Methodsmentioning
confidence: 99%
“…A total of 10 studies described event-contingent mEMDA methods used in nutrition-related research [52][53][54][55][56][57][58][59][60][61]. Additional approach details were extracted from other related journal articles [43,[62][63][64][65][66][67][68][69][70][71][72][73].…”
Section: Summary Of Event-contingent Studiesmentioning
confidence: 99%
See 2 more Smart Citations